Macular Thickness Fluctuations in Eyes With Diabetic Macular Edema Treated With Intravitreal Steroid - Roan, Vivian D (Ophthalmic surgery, lasers & imaging retina, 2023)
BACKGROUND AND OBJECTIVE: Macular thickness fluctuations (MTF) over time may be more predictive of visual outcomes than absolute macular thickness in patients with diabetic macular edema (DME) treated with anti-vascular endothelial growth factor (anti-VEGF). It is unclear whether this association exists in DME patients treated with intravitreal steroids or whether steroids confer reduced MTF versus anti-VEGF treatments